Komposisi, Keragaman dan Profil Tanaman Agroforestri di Taman Hutan Raya Wan Abdul Rachman (Composition, Diversity, and Profile of Agroforestry Plants in Wan Abdul Rachman Grand Forest Park) - Murniati - Murniati; Minarningsih Minarningsih (Jurnal Penelitian Hutan Tanaman, 2022)
ABSTRACT At Wan Abdul Rachman Grand Forest Park (WAR GFP), an agroforestry system has been developed to repair the degraded conservation forest. In 2018 and 2019, the research was carried out at the WAR GFP and two surrounding villages, Bogorejo and Cilimus, which are located in Pesawaran District, Lampung Province. The research aimed to identify the soil fertility, as well as the species composition, diversity, and vegetation profiles of the agroforestry system. Interviews with respondents and key informants as well as field measurements were used in the research. Key informants consisted of the manager of WAR GFP, the heads village, and the head of farmer group alliances. Respondents were selected randomly from forest farmer groups in the two villages. In the agroforestry area, there were three clusters of plant species that were present: forest trees, multi-purpose tree species (MPTS,) and understorey plants. MPTS, which had a density of 1,077 trees/ha, was the dominant plant cluster. With an H’ value (Shannon Diversity Index) of 1.694S, the agroforestry system had a moderate level of species diversity. The average base area was 29.44 m2/ha, and there was a fairly high average tree cover. The level of soil fertility, including less fertile. At the research site, the agroforestry system’s plant characteristics were approximately similar to the characteristics of forest vegetation. As a result, it might be developed extensively on a large scale in forest areas, either in protected forests or conservation forests.Keywords: multi-strata, species diversity, basal area, profile, soil fertilityABSTRAK Sistem agroforestri telah dikembangkan di Taman Hutan Raya Wan Abdul Rachman (Tahura WAR) sebagai upaya merestorasi kawasan hutan tersebut. Budi daya tanaman semusim ditransformasi secara bertahap menjadi sistem agroforestri multi-strata. Penelitian dilaksanakan di Tahura WAR dan dua desa sekitarnya, yaitu Desa Bogorejo dan Desa Cilimus, Kabupaten Pesawaran, Provinsi Lampung pada tahun 2018 dan 2019. Penelitian bertujuan untuk mengidentifikasi komposisi jenis, keragaman dan profil vegetasi/tanaman di areal agroforestri, dan kesuburan tanah. Penelitian dilakukan melalui diskusi dan wawancara dengan informan kunci dan petani agroforestri, serta pengukuran lapang berupa analisis dan pemetaan vegetasi/tanaman. Informan kunci terdiri atas pengelola Tahura WAR, Kepala Desa dan Ketua Gabungan Kelompok Tani. Responden petani agroforestri sebanyak 59 orang dipilih secara acak dari beberapa kelompok tani hutan di dua desa lokasi penelitian. Terdapat tiga kelompok tanaman di petak agroforestri, yaitu jenis pohon hutan, jenis pohon serba guna (JPSG) dan tanaman bawah. JPSG atau Multi Purpose Tree Speises (MPTS) merupakan kelompok tanaman yang dominan dengan kerapatan 1.077 pohon/ha. Keragaman jenis tanaman pada sistem agroforestri termasuk sedang. Rata-rata basal area adalah 29,44 m2/ha dan rata-rata tutupan pohon termasuk sangat tinggi. Tingkat kesuburan tanahnya termasuk kurang subur. Karakteristik tanaman pada sistem agroforestri di lokasi penelitian mendekati atau hampir sama dengan karakteristik vegetasi hutan, sehingga dapat dikembangkan pada skala luas di kawasan hutan, baik hutan lindung maupun hutan konservasi.Kata kunci: Multi-strata, keragaman jenis, basal area, profil, kesuburan tanah